ONSET OF A BOTTLENECK ? The Permitting and Regulation of New Mining Projects - The Western Canadian Experience (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
What Bottleneck? ??Resurgence of BC Mining Industry; ??Climate of heightened activity ?Increases pressure placed upon regulatory agencies; ??Current EA and permitting system, when Federal agencies are involved, remains duplicative and inefficient ?not necessarily leading to better decision making; ??Inefficiencies will impederecovery